Multiscale neural gradients reflect transdiagnostic effects of major psychiatric conditions on cortical morphology - Bo-yong Park; Valeria Kebets; Sara Larivière; Meike D. Hettwer; Casey Paquola; Daan van Rooij; Jan Buitelaar; Barbara Franke; Martine Hoogman; Lianne Schmaal; Dick J. Veltman; Odile A. van den Heuvel; et al. (Communications Biology, 2022)
Individuals across six major psychiatric conditions from the ENIGMA consortium reveals a shared morphological effect, following a sensory-fugal axis, which is related to microstructural gradient and neurotransmitter axes.